Intern Placement and Monitoring System at SMK YP Gajah Mada Palembang - Faridiansyah, M.Faridiansyah; Irawan, Dedi; Purnamasari, Susan Dian; Suyanto, Suyanto (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
In today's technological era, web-based solutions are essential for optimizing the distribution of internship placements. The current manual processes can lead to issues such as placement delays and difficulties in data collection. This research proposes the implementation of a web-based system to streamline the internship program at SMK YP Gajah Mada, focusing on developing an efficient and user-friendly platform. The objective of this research is to build a web-based internship placement and monitoring system at SMK YP Gajah Mada Palembang. The methodology used in this study is Rapid Application Development (RAD), an alternative to traditional system life cycles. The implementation of this system is expected to improve placement processes, enhance data management, and provide a more effective way to monitor and support interns throughout their program. The results of the research indicate that the web-based system significantly reduces placement delays, facilitates data collection, and offers a structured approach to monitoring and managing internship activities.